Labelling of proteinaceous binders in art - Yin, Ooi Su (2019)
Easel paintings are important Cultural Heritage assets with significant historic and cultural value. They usually possess a multi-tiered structure, composed of different layers, some of which may present protein binders. Proteins have been commonly used as paintings medium, adhesives and coating layers in easel paintings. Hence, their recognition is a crucial step for easel painting’s conservation and restoration processes. The present work presents a novel fluorescent labelling methodology, using a coumarin derivative chromophore, C392STP (sodium (E/Z)-4-(4-(2-(6,7- dimethoxycoumarin-3-yl)vinyl)benzoyl)-2,3,5,6-tetrafluorobenzenesulfonate) as a fluorophore probe to bond proteinaceous binders used in paintings. The method was developed and optimized using commercial proteins and proteins extracted from hen’s egg yolk and white, bovine milk, and rabbit skin. In order to mimic the real conditions, paint models of easel paintings have been prepared by mixing proteins such as ovalbumin, casein and rabbit glue with different pigments (lead white, chrome yellow and black bone) and the fluorescent labelling method was miniaturized and tested. The results revealed that proteins in concentration as low as 6.0 μg/ml could be detected. Finally, for validation methodology, real micro samples of easel paintings were analyzed. The extracted proteins were submitted to the fluorescent labelling method developed and clearly identified in electrophoretic profiles. The results evidence the applicability of this methodology as an effective and useful analytical tool for the identification of protein binders obtained from easel paintings and, possibly in other art work. Additionally, theoretical quantum chemical calculations based on the Density Functional Theory (DFT) and Time Dependent Density Functional Theory (TD-DFT) have been performed in the C392STP coumarin and in a related coumarin derivative ((E/Z)-4-(2-(6,7- dimethoxycoumarin-3- yl)vinyl)-N-propylbenzamide), that mimics the coumarin bonded to lysine. The calculations confirm the experimental trends in absorption wavelengths and are in good agreement with the experimental absorption spectra, providing a comprehensive characterization of the main spectral features of the studied compounds; RESUMO: Identificação de ligantes proteicos em arte As pinturas de cavalete são um componente importante do Património Cultural, com um significativo valor histórico e cultural. Geralmente possuem uma estrutura composta por diferentes camadas, algumas das quais podem apresentar ligantes proteicos. As proteínas surgem geralmente em pinturas de cavalete como meio de suporte da pintura, adesivos e camadas de revestimento. A sua identificação é, portanto, um passo crucial para os processos de conservação e restauração da pintura de cavalete. O presente trabalho apresenta uma nova metodologia de marcação fluorescente, utilizando um cromóforo derivado da cumarina, C392STP ((E/Z)-4-(2-(6,7- dimetoxicoumarin-3-yl)vinil)-N-propilbenzamida) como sonda fluorescente para marcar os ligantes proteicos usados em pinturas. O método foi desenvolvido e otimizado utilizando proteínas comerciais e proteínas extraídas da gema e clara de ovo de galinha, de leite de bovino e de pele de coelho. Para simular as condições reais, foram preparados modelos de pintura de pinturas de cavalete, misturando-se proteínas como ovalbumina, caseína e cola de coelho, com diferentes pigmentos (branco de chumbo, amarelo de crómio e negro de osso) e o método de marcação fluorescente foi miniaturizado e testado. Com base nos resultados obtidos, o método revelou-se capaz de detetar proteínas a concentração tão baixa quanto 6,0 μg / ml. Finalmente, para validação do método, foram analisadas micro amostras reais de pinturas de cavalete. As proteínas extraídas foram submetidas ao método de marcação fluorescente desenvolvido, tendo sido claramente identificadas em perfis eletroforéticos. Os resultados evidenciam a aplicabilidade desta metodologia como uma ferramenta analítica eficaz e útil para a identificação de ligantes proteicos extraídos de pinturas de cavalete e, possivelmente, de outras obras de arte. Adicionalmente, foram realizados cálculos quânticos baseados na Teoria Funcional da Densidade (DFT) e na Teoria do Funcional da Densidade Dependente do Tempo (TD-DFT) da cumarina C392STP de um derivado desta cumarina, ((E/Z)-N-propyl-4-(2-(6,7-dimethoxy-2-oxo-2H-chromen-3-yl)vinyl)benzamide)), que modela a cumarina ligada a lisina. Os cálculos confirmam as tendências experimentais observadas nos comprimentos de onda de absorção e estão de acordo com os espectros de absorção experimentais, fornecendo uma caracterização abrangente das principais características espectrais dos compostos estudados.